PENERAPAN STRATEGI PEMBELAJARAN THINK TALK WRITE BERBASIS KONTEKSTUAL UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS SISWA KELAS X-8 SMA NEGERI 1 SUKOHARJO TAHUN PELAJARAN 2010/ 2011 - Ningsih, Dwi Untari; Santosa, Slamet; Sugiharto, Bowo (Pendidikan Biologi, 2011)
ABSTRACT ? This research aims toimprovebiologi?s  science skill process towards students in grade of X-8 of SMA Negeri 1 Sukoharjoby implementation of Think Talk Write strategy based on contextual learning. This research belongs to Classroom Action Research. Qualitative research paradigm is used asan approach to view all the obtained data.This Classroom Action Research is performed and consist of3 cycles. Each cycles consist of four stages namely planning, implementation, observation, and reflection. Data for each cycle were gathered by using 3 kinds of data collection procedures, questionnaires, observations, and interviews. All the obtained data then were analyses descriptively to ascertain whether the applications of Classroom Action Research is considered as effective or otherwise. From the results, it can be concluded that the implementation of Think Talk Write strategy based on contextual learningtowards students of class X-8 SMA Negeri 1 Sukoharjo academic year 2010/2011 has given a good effect. According to theobservationof student activities indicators is rise from  62,25% to the 77,08% during the 1st Cycle and rise up to 82,25% during the last Cycle. As compare to the previous observationthe result of thequestionnaireupon the same indicators is rise from 65,02% to the 70,69%duringthe 1st Cycle and ended with  77,55 % during the last Cycle. Yet it can be concluded that the application of Think Talk Write strategy based on contextual learning could improve the science skill process. Keywords: Think Talk Write, Contextual, Science Skill Process